Modulation masking for recurrent low-noise noise masker - Kutzner, D. J. (Archives of Acoustics, 2006)
The main purpose of these investigations was to examine modulation masking phenomenon for recurrent low-noise noise masker. Such masker is characterized by three parameters, namely: repetition frequency, frep, centre frequency, fo, and bandwidth, b. The parameter frep is not reflected in the signal power spectrum and is related to the autocorrelation period. The parameters fo and b describe spectral properties of the interfering signal, i.e. localization and concentration of its power in the frequency domain. In order to separate possible effects of the masker temporal repetition and its spectral parameters, modulation masking measurements were carried out for fo=64 Hz, b=16 Hz and frep=1 s-1 (without repetition), 4 s-1 and 8 s-1 and probe signal of frequencies fp=1, 2, 4, 6, 8, 12, 16, 32, 52 and 64 Hz. The masker rms modulation depth was 30%; carrier signal was a 4-kHz sinusoid. The main conclusion is that modulation masking patterns are determined by the spectral properties of the masker.